2015
DOI: 10.1186/s40064-015-1541-2
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional study: the knowledge, attitude, perception, misconception and views (KAPMV) of adult family members of people living with human immune virus-HIV acquired immune deficiency syndrome-AIDS (PLWHA)

Abstract: We intended to assess knowledge, attitude, perception, misconception and views (KAP-MV) of family members of PLWHA. A cross-sectional retrospective study conducted in Anti-retroviral centre of Mahatma Gandhi Memorial—MGM hospital, Warangal, Telangana, South-India from July to September 2014. A questionnaire containing 41 items was distributed among adult family members accompanying patients living with HIV/AIDS-PLWHA. Level of KAP-MV was categorized into poor (0–28), average (29–55) and good (56–82). Analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 21 publications
9
16
0
Order By: Relevance
“…Furthermore, the data revealed that, amongst those women, who heard of HIV/AIDS, the majority (68%) have high overall HIV/AIDS knowledge and more than 55% express positive attitudes towards PLWHAs. These results are consistent with previous research conducted in South India, where most of the respondents had good knowledge about HIV/AIDS and had positive attitudes towards PLWHAs [43]. Similarly, studies conducted in Karachi (Pakistan) [44] and across Pakistan [16] also reported good knowledge about HIV/AIDS among respondents.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, the data revealed that, amongst those women, who heard of HIV/AIDS, the majority (68%) have high overall HIV/AIDS knowledge and more than 55% express positive attitudes towards PLWHAs. These results are consistent with previous research conducted in South India, where most of the respondents had good knowledge about HIV/AIDS and had positive attitudes towards PLWHAs [43]. Similarly, studies conducted in Karachi (Pakistan) [44] and across Pakistan [16] also reported good knowledge about HIV/AIDS among respondents.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding the associated socio-demographic factors, our research further found that overall knowledge of HIV/AIDS is higher amongst women with higher education, residing in urban areas, having exposure to mass media and belonging to the richest wealth quintile. These findings are comparable to studies conducted in India [15, 43], Bangladesh [45] and Ethiopia [40]. Similar results were seen regarding women’s attitudes towards PLWHAs.…”
Section: Discussionsupporting
confidence: 88%
“…This study results in good knowledge of HIV/AIDS in most of the respondents. The result is similar to most of the families of HIV patients who have a good level of knowledge about HIV/AIDS, 5 as well as study in Turkey 6 involving undergraduate health science students.…”
Section: Discussionsupporting
confidence: 70%
“…Three hospital nurses who were trained as research assistants conducted the interviews in the native language of the participants using a structured questionnaire which was adapted from an earlier WHO AIDS Questionnaire. 22 A pilot study was conducted to pre-test the questionnaire with 15 HIV-positive mothers at the Mabote clinic. Each completed questionnaire was checked manually by the research assistants, and subsequently quality checked and captured into an Excel spreadsheet by the principal investigator (PI) at the end of each day.…”
Section: Methodsmentioning
confidence: 99%